Characterization of a pulsed injection-locked Ti:sapphire laser and its application to high resolution resonance ionization spectroscopy of copper. (24th July 2017) - Sonnenschein, V; Moore, I D; Raeder, S; Reponen, M; Tomita, H; Wendt, K
Abstract: A high repetition rate pulsed Ti:sapphire laser injection-locked to a continuous wave seed source is presented. A spectral linewidth of 20 MHz at an average output power of 4 W is demonstrated. An enhanced tuning range from 710–920 nm with a single broadband mirror set is realized by the inclusion of a single thin birefringent quartz plate for suppression of unseeded emission. The spectral properties have been analyzed using both a scanning Fabry–Pérot interferometer as well as crossed beam resonance ionization spectroscopy of the hyperfine levels of natural copper. Delayed ionization of the long-lived excited state is demonstrated for increased resolution. For the excited state hyperfine coupling constant of the 244 nm 4s 2 S 1 / 2 → 4s4p 4 P° 1 / 2 ground-state transition in 63 Cu, a factor of ten reduction in error compared to previous literature was achieved. The described laser system has been in operation at several radioactive ion beam facilities.